Genetic variation in the β2-adrenocepter gene is associated with susceptibility to bacterial meningitis in adults. - Kirsten S Adriani; Matthijs C Brouwer; Frank Baas; Aeilko H Zwinderman; Arie van der Ende; Diederik van de Beek (PLoS ONE, 2012)
Recently, the biased β2-adrenoceptor/β-arrestin pathway was shown to play a pivotal role in crossing of the blood brain barrier by Neisseria meningitidis. We hypothesized that genetic variation in the β2-adrenoceptor gene (ADRB2) may influence susceptibility to bacterial meningitis. In a prospective genetic association study we genotyped 542 patients with CSF culture proven community acquired bacterial meningitis and 376 matched controls for 2 functional single nucleotide polymorphisms in the β2-adrenoceptor gene (ADRB2). Furthermore, we analyzed if the use of non-selective beta-blockers, which bind to the β2-adrenoceptor, influenced the risk of bacterial meningitis. We identified a functional polymorphism in ADRB2 (rs1042714) to be associated with an increased risk for bacterial meningitis (Odds ratio [OR] 1.35, 95% confidence interval [CI] 1.04-1.76; p = 0.026). The association remained significant after correction for age and was more prominent in patients with pneumococcal meningitis (OR 1.52, 95% CI 1.12-2.07; p = 0.007). For meningococcal meningitis the difference in genotype frequencies between patients and controls was similar to that in pneumococcal meningitis, but this was not statistically significant (OR 1.43, 95% CI 0.60-3.38; p = 0.72). Patients with bacterial meningitis had a lower frequency of non-selective beta-blockers use compared to the age matched population (0.9% vs. 1.8%), although this did not reach statistical significance (OR 1.96 [95% CI 0.88-4.39]; p = 0.09). In conclusion, we identified an association between a genetic variant in the β2-adrenoceptor and increased susceptibility to bacterial meningitis. The potential benefit of pharmacological treatment targeting the β2-adrenoceptor to prevent bacterial meningitis in the general population or patients with bacteraemia should be further studied in both experimental studies and observational cohorts.